Expression patterns of estrogen and androgen receptors in NSCLC patients according to the PD-L1 profile - Rodriguez-Lara, Vianey; Cortés-Ramírez, Gala; Angeles-Torres, Itzel Amayrani; Rodriguez-Cid, Jeronimo; Pedraza-Reyes, Sally María Luisa; Avila-Costa, Maria Rosa; Ordoñez-Librado, José Luis; Cerbón, Marco (Frontiers in Immunology, 2025)
BackgroundLung cancer is the leading cause of cancer-related death worldwide, with non-small cell lung cancer (NSCLC) being the most common type. Immunotherapy targeting programmed death ligand-1 (PD-L1) blockade has significantly improved survival, but differences in responses by sex have been reported, suggesting a possible role of sex hormones. Estrogens and androgens, through their receptors support lung carcinogenesis, but their role in immune evasion via the PD-1/PD-L1 pathway remains poorly understood.Materials and MethodsWe analyzed by immunohistochemistry the expression patterns of estrogen receptors (ERα and ERβ) and androgen receptor (AR) in 95 PD-L1-positive (PD-L1+) and 72 PD-L1 negative (PD-L1-) NSCLC patients by sex and hormonal status. We also investigated associations between hormonal receptors, PD-L1 profile, PD-L1 tumor proportion score (TPS), and clinical features (cancer stage according to the TNM stage of cancer, smoking history, wood smoke exposure, and asbestos exposure).ResultsERβ was the predominant form of estrogen receptor in PD-L1- patients, while ERα expression was significantly higher in PD-L1+ patients and strongly associated with the PD-L1+ profile, regardless of sex or hormonal status. AR expression was low across all groups and showed no association with PD-L1. Among PD-L1+ patients, ERα expression levels were highest in premenopausal women, followed by men and postmenopausal women. ERα levels in the PD-L1+ group, were not associated with PD-L1 TPS or with clinical features.ConclusionThe estrogen pathway, particularly via ERα, plays a key role in PD-L1 expression and may contribute to tumor immune evasion. Antiestrogen therapy could represent a promising strategy to enhance immunotherapy efficacy in patients expressing ERs.